Kadar Besi (Fe) pada Tanaman Bayam Cabut (Amaranthus tricolor L.) yang Ditanam pada Beberapa Media Tanah Bekas Galian Tambang Batubara di Samarinda - Annisa Annisa; Dwi Susanto; Sudrajat Sudrajat (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
This research aims to find out if there is a correlation between the availability of Fe on the soil of an excavated coal mine with Fe levels in spinach. This research out by experiment Completely Randomized Design consists of 5 treatment is P0 (soil media in Kebun Raya Unmul Samarinda), P1(soil media in Sambutan ), P2 (soil media in Batu Besaung ), P3 (soil media in Loa Bakung) and P4 (soil main excavated + soil media in Kebun Raya Unmul Samarinda with comparison 1:1) with repotition 4 unit polybag and each units consists of 10 seeds of spinach. The Plants maintained for 5 weeks and parameters measured is growth of plant height, leaf number, leaf colour, Fe content in the spinach and Fe content in this soil media. The results showed that the mine excavated soil with the average levels of Fe contains for 39,9598 µg/mL; 30,9458 µg/mL; 31,2599 µg/mL dan 28,502 µg/mL, consecutive to the origin of former soil mine samples is soil main excavated in Sambutan, Batu besaung, Loa bakung and soil mixture of all mines with the ground control (Kebun Raya Unmul). Soil main excavated is not good be used as a growing medium with the addition of fertilizer NPK. The availability of Fe elements in the soil followed by increased Fe levels in the spinach by the equation of guess regression y = 0,004x + 0,139 and value r = 0,902 on the significant levels 0,005.